Penerapan Konsep Green Marketing dalam Menghasilkan Produk yang Ramah Lingkungan: Sebuah Kajian Konseptual Sebagai Panduan Bagi Peneliti - Andri Yandi; Imam Muklhlis; Arief Noviarakhman Zagladi (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study raises environmental and sustainability issues. This research consists of several parts. First, the literature review focuses on green marketing orientation. Second, the research model and propositions developed in this study are based on a literature review of previous studies, such as the relationship between green marketing orientation towards green innovation and green competitive advantage, the relationship between green innovation and green marketing performance and green competitive advantage, and the relationship between excellence. environmentally friendly competitive. Next, environmentally friendly marketing performance is explored and linked to environmentally friendly marketing performance. In the context of a green marketing orientation strategy, an important role of social marketing theory is that organizational awareness in producing environmentally friendly products is very important for building sustainable competitive advantages in the long term. Thus, this research also shows that environmentally friendly product innovation and environmentally friendly competitive advantages are important strategies for reducing environmentally friendly organizational behavior.